Linking drivers of food insecurity and ecosystem services in Africa - Aryee, Gregory Ayitey; Sardinha, Idalina Dias; Branquinho, Cristina (Frontiers in Sustainable Food Systems, 2024)
Food insecurity is a multidimensional and intricate problem, known to have significant implications for individuals, communities, and countries worldwide. Africa has become the continent that is experiencing this uncertainty the most. Food Security (FS) encompasses several aspects such as availability, accessibility, nutrient use, and supply system stability with time and, more recently, other obliges to governance/agency and sustainability. Knowing the interconnection between these aspects and the Ecosystems Services (ES) and understanding the relationship and interactions between FS and ES is important. Moreover, this knowledge may contribute to supporting policies that promote long-term sustainable and secure food systems. Hereby, a conceptual framework is presented, that examines interactions between food insecurity drivers and ecosystem change drivers and the combined influence on ES. Our review further introduces existing trade-offs between ES on account of agricultural intensification vs. key existing strategies to promote sustainable agricultural production. These strategies include climate-smart agriculture, sustainably managed land, and effective handling of water resources. In the end, the potential of Payment for Ecosystem Services (PES), as a suitable approach to ensuring these strategies are adopted, especially in African countries where sustainable financial incentives are currently under-explored is discussed. In resume, this review aims to make a conceptual contribution to understanding how drivers of food insecurity influence drivers of ecosystem changes, the impact of these influences on the services of ecosystems, and how sustainable agro approaches and PES introduction can help to reduce such negative impacts.